TINJAUAN YURIDIS KEWENANGAN PENGELOLAAN DAN PENGEMBANGAN PELABUHAN PENYEBERANGAN BALOHAN SABANG - Rachmatika Lestari; Apri Rotin Djusfi; Phoenna Ath Thariq (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
In the context of developing the Sabang Free Trade Zone and Free Port, it is necessary to revitalize the development of the Balohan Crossing Port of Sabang City. However, based on Article 11 PP Number 69 of 2001 concerning Ports, it is stated that the management of national, international ports and hub ports is left to BUMN, in this case PT. Indonesian Port (Pelindo). Whereas on the other hand, Law No. 32 of 2004 and Law No. 34 of 1999 indicates the transfer of authority from the central government to regional governments, including in terms of port management. The same is true in the context of Aceh's autonomy, based on Law No. 11 of 2006 concerning the Government of Aceh states that there is a surrender of wider authority to the regions to manage their own household affairs. The problem in this research is how is the authority to operate a port based on positive law in Indonesia? What is the authority for managing regional feeder ports in the context of Aceh's special autonomy? And what are the procedures for the utilization and management of the Balohan crossing port? The method used in this study is a nominative juridical research method. The results of the study showed that the authority to operate the port was technically regulated in Government Regulation No. 61 of 2009 concerning Ports. In the context of Aceh's special autonomy, Law No. 11 of 2006 concerning Aceh Government and PP No. 23 of 2015 concerning National Government Authority in Aceh in the context of Aceh's special autonomy, wasn’t mentioned in detail regarding port management according to the type of hierarchy, but only mentioned regarding port management (in general) managed by BUMN in which the management is managed with the Aceh Government and / or Regency / City Government. Even though the Act and PP aren’t mentioned in detail, the procedures for the utilization and management of the Balohan crossing port can be seen in the Minister of Transportation Decree Number KP. 432 of 2017 concerning the Establishment of a National Port Master Plan. The Ministry of Transportation stated that the Port of Balohan Sabang occupied the PL (Local Feed Port) hierarchy. This means that the Regency / City Government in Prov. Aceh has the authority to manage the Balohan Port in Sabang legally justified and allowed by law.Keywords: authority, management and development, balohan port